Bahaya Risiko Kecelakaan Kerja Terkena Tumpahan Cairan Kimia di Laboratorium Klinik Perguruan Tinggi di Kota Semarang - Salwa, Syarifah Janatu; Lestari, Anjani Dwi Ayu (Poltekkes Kemenkes Palembang, 2025)
The laboratory is one of the educational infrastructures, which can be used as a place for students to practice understanding concepts by conducting experiments and observations. The use of chemicals in clinical laboratories requires special attention to worker safety, therefore, strict Standard Operating Procedures (SOPs) are needed to protect officers from potential exposure to the chemical liquids used, this SOP includes procedures for using personal protective equipment (PPE) properly and correctly, arranging storage of hazardous chemicals in safe places and others. The purpose of the research conducted at the Clinical Laboratory of the Muhammadiyah University of Semarang was to identify hazards and evaluate occupational safety risks while in the laboratory. The research method we conducted at the Muhammadiyah University of Semarang is qualitative. The method used is descriptive qualitative. The results of interviews with informants, the main treatment carried out when exposed to chemical liquids is to wash the affected area with running water for 15 minutes. The SOP carried out at the Muhammadiyah University is in accordance with existing laboratory standards. The laboratory arrangement has also complied with existing standards in the laboratory.